High Prevalence Fluke Infection at Four Cattle Farms Located in Kuala Terengganu, Malaysia - Khadijah Saad,; Mohammad Faiz M,; Rita Nadarasan,; Mursyidah A K ,; Quaza Nizamuddin Hassan, (Tropical Life Sciences Research, 2019)
A survey was conducted to determine the presence of parasitic worm infection in cattle at four farms located in Kampung Surau Haji Daud, Kampung Kubang Jela, Kampung Gemuruh and Kampung Peradong, Kuala Terengganu. Thirty-three faecal samples and blood samples were obtained from each cattle involved in this survey. Faecal samples were subjected to sedimentation method, modified McMaster method and faecal culture to detect trematode eggs, nematode eggs, and to identify the third stage of larvae. Blood samples were subjected to Packed Cell Volume (PCV) method to determine if the cattle are anaemic, normal or dehydrated. Result indicated that out of 33 cattle examined 17% of the cattle were positive for liver fluke, 67% were positive for stomach fluke and 42% were positive for nematode infection. PCV value indicated that all the cattle examined are not anaemic or dehydrated. The results obtained showed that trematode and nematode infections are common problem in all the four farms. The results were submitted to Department of Veterinary Services to plan further action and treatment. Satu kajian telah dijalankan untuk mengetahui kehadiran cacing parasit pada lembu di empat ladang di Kampung Surau Haji Daud, Kampung Kubang Jela, Kampung Gemuruh dan Kampung Peradong, Kuala Terengganu. Sebanyak 33 sampel tinja dan darah telah diambil daripada lembu yang terlibat dalam kajian ini. Sampel tinja diproses dengan kaedah pemendapan, kaedah McMaster yang telah diubah suai, dan kultur tinja, untuk mengesan telur trematod, nematod dan juga untuk mengenal pasti larva peringkat ketiga. Sampel darah diproses dengan kaedah Packed Cell Volume (PCV) untuk mengetahui sama ada lembu adalah anemik, normal atau mengalami dehidrasi. Keputusan menunjukkan bahawa daripada 33 ekor lembu yang diperiksa, 17% daripadanya adalah positif untuk cacing fluk hati, 67% adalah positif untuk cacing fluk perut, dan 42% adalah positif untuk jangkitan nematod. Nilai PCV menunjukkan bahawa tiada lembu yang anemik atau mengalami dehidrasi. Keputusan menunjukkan bahawa jangkitan trematod dan nematod adalah masalah yang dihadapi oleh keempat-empat ladang. Keputusan telah dihantar ke Jabatan Perkhidmatan Veterinar untuk rawatan dan tindakan seterusnya.